Evaluation of Inflammation-Related Proteins in Multiple Sclerosis Disease with Relapses and Remissions - Nisa Hocaoğlu; Nur Damla Korkmaz; Birsen Elibol; Zehra Cemre Karakayalı; Şule Terzioğlu-Uşak; Azize Esra Gürsoy (Turkish Journal of Immunology)
Objective: Multiple sclerosis (MS) is an autoimmune disease affecting the brain and spinal cord by demyelination and neurodegeneration. Although the cause of the disease is not known exactly due to its heterogeneous etiology, it is thought that inflammatory processes can be effective in the formation and progression of the MS pathology. Herein, the present study's aim was to evaluate the changes in inflammation-related proteins, which have a crucial role in the formation of neuroinflammation, according to the period of MS. Materials and Methods: The study included 33 MS patients, 8 of whom were in relapse and 25 in remission, and 10 healthy individuals. Lymphocytes were isolated from peripheral blood. After RNA isolation and cDNA conversion, NLRP3, ASC, NLRX1, IL-1β, and IL-18 gene expressions were measured in real time-polymerase chain reaction. In addition, the protein levels of the NLRP3 and ASC were determined from serum samples by enzyme-linked immunosorbent assay. Results: The expression of the NLRX1 gene was significantly decreased in the patient groups compared to the controls. The levels of NLRP3, ASC, and IL-18 gene expressions of patients were not significantly different from controls in the remission and relapse periods. Although IL-1β gene expressions of the patients in the remission period increased in value, it was not statistically significant compared to that of healthy controls. Conclusion: Our findings showed that anti-inflammatory NLRX1 protein can be considered as a strong biomarker in the diagnosis and treatment of MS, where neuroinflammation is the main cause.